THE 'FUNKTIONALE KONTORECHNUNG' OF WALTER THOMS. - Holzer, H. Peter; Schönfeld, Hanns-Martin (The Accounting Review, 1964)
The article focuses on German accounting literature. The "Kontentheorien," which were developed in German-speaking countries attempt to explain, often through mathematical analysis, the double entry mechanism of accounting. They are only indirectly related to the various balance sheet theories, which deal principally with the form and substance of financial statements and are largely centered around the valuation problem and income determination. German accounting literature includes many excellent works on "Rontentheorie." One of the more recently proposed theories in this area is the "funktionale Kontorechnung" by Walter Thorns, whose proponents claim that it has already been usefully applied in numerous German companies. One of the more interesting features of the Thorns system is the proposed treatment of cash transaction data. It is the purpose of the paper to acquaint the reader with this system of accounting and types of analysis, which are an immediate by-product of its application. What is new and different in the system is the fact that cash is considered to be in a category all by itself.